Improving the Visualisation of Renal Blood Test Results to Enhance Patient – Clinician Communication. (28th July 2017) - Gradinar, Adrian; Davenport, Jeremy; Hill, Heather; Coulton, Paul
Abstract: Dialysis patients in the UK usually undergo routine monthly blood tests which support the medical team in assessing their ongoing condition. Based on these results, clinicians then advise the patients on appropriate changes to diet and/or medication to improve their health. Whilst the results of these blood tests can be made available to the patient via an online patient portal, their presentation is primarily numerical. While this style is applicable to medical professionals who are able to interpret such results, it is less accessible to patients, restricting their ability to readily engage with their own results. This research presents a collaborative design approach aimed to produce alternative ways of visualising blood test results that meet both the needs of clinicians and the patient with the aim of enabling patients to be more actively involved in managing their own condition.